2019
DOI: 10.3892/ijmm.2019.4233
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the regulatory role of ORMDL3 in airway barrier dysfunction using in vivo and in vitro models

Abstract: The airway epithelium (AE) is the main protective barrier between the host and external environmental factors causing asthma. Allergens or pathogens induce AE dysfunction, including epithelial permeability alteration, trans-epithelial electrical resistance (TEER) reduction, upregulation of inflammatory mediators and downregulation of junctional complex molecules. Orosomucoid-like protein isoform 3 (ORMDL3), a gene closely associated with childhood onset asthma, is involved in airway inflammation and remodeling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…Occludin and ZO-1 were detected as they play an indispensable role in regulating barrier tightness and a critical role in the establishment of airway belt-like TJs, respectively ( Furuse, 2010 ; Matter and Balda, 2014 ). Claudin-18, a lung-specific claudin that is highly associated with airway epithelial barrier dysfunction in asthma, was also detected ( Sweerus et al, 2017 ; Yang et al, 2019 ). To further assess whether the disruption in occludin, ZO-1, and claudin-18 occurred because of additional pressure exposure, we first investigated cellular occludin, ZO-1, and claudin-18 by western blot assay.…”
Section: Resultsmentioning
confidence: 99%
“…Occludin and ZO-1 were detected as they play an indispensable role in regulating barrier tightness and a critical role in the establishment of airway belt-like TJs, respectively ( Furuse, 2010 ; Matter and Balda, 2014 ). Claudin-18, a lung-specific claudin that is highly associated with airway epithelial barrier dysfunction in asthma, was also detected ( Sweerus et al, 2017 ; Yang et al, 2019 ). To further assess whether the disruption in occludin, ZO-1, and claudin-18 occurred because of additional pressure exposure, we first investigated cellular occludin, ZO-1, and claudin-18 by western blot assay.…”
Section: Resultsmentioning
confidence: 99%
“…90 Yang et al 91 showed that high levels of ORMDL3 attenuated claudin 17 and E-cadherin protein levels in vitro on primary bronchial and 16HBE bronchial epithelial cells, and in an asthma mouse model, whereas inhibition of ORMLD3 reconstituted epithelial barrier integrity. 91 This process was mediated via the activation of sphingosine kinase 1 and ERK, which are involved in TJ disruption. 92 The genetic signature cannot only explain the increasing incidence and prevalence of airway diseases.…”
Section: Genetic and Epigenetic Factorsmentioning
confidence: 99%
“…Soluble isoform, IL-1RL1-a or sST2, acts as a decoy receptor by sequestering IL-33, thereby inhibiting IL1RL1-b/IL-33 signaling, which could be used as a biomarker or target for pharmacological intervention. 133,134 Orosomucoid-like 3 (ORMDL3), was shown to play an important role in regulating epithelial barrier function in allergic asthma, [135][136][137] rhinovirus infection 138,139 and by inducing the p-ERK/MMP-9 pathway to promote pathological airway remodeling in patients with asthma. 140 SMAD3 is an essential signal transducer in TGF-β signaling, which is elevated in airway epithelial cells of some asthmatics 141,142 and is involved in the response of bronchial epithelial cells to viral infection.…”
Section: Genetic and Epigenetic Changes In Bronchial Epitheliummentioning
confidence: 99%